Minor Cannabinoids: Biosynthesis, Molecular Pharmacology and Potential Therapeutic Uses - Walsh, Kenneth B.; McKinney, Amanda E.; Holmes, Andrea E. (Frontiers in Pharmacology, 2021)
The medicinal use of Cannabis sativa L. can be traced back thousands of years to ancient China and Egypt. While marijuana has recently shown promise in managing chronic pain and nausea, scientific investigation of cannabis has been restricted due its classification as a schedule 1 controlled substance. A major breakthrough in understanding the pharmacology of cannabis came with the isolation and characterization of the phytocannabinoids trans-Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD). This was followed by the cloning of the cannabinoid CB1 and CB2 receptors in the 1990s and the subsequent discovery of the endocannabinoid system. In addition to the major phytocannabinoids, Δ9-THC and CBD, cannabis produces over 120 other cannabinoids that are referred to as minor and/or rare cannabinoids. These cannabinoids are produced in smaller amounts in the plant and are derived along with Δ9-THC and CBD from the parent cannabinoid cannabigerolic acid (CBGA). While our current knowledge of minor cannabinoid pharmacology is incomplete, studies demonstrate that they act as agonists and antagonists at multiple targets including CB1 and CB2 receptors, transient receptor potential (TRP) channels, peroxisome proliferator-activated receptors (PPARs), serotonin 5-HT1a receptors and others. The resulting activation of multiple cell signaling pathways, combined with their putative synergistic activity, provides a mechanistic basis for their therapeutic actions. Initial clinical reports suggest that these cannabinoids may have potential benefits in the treatment of neuropathic pain, neurodegenerative diseases, epilepsy, cancer and skin disorders. This review focuses on the molecular pharmacology of the minor cannabinoids and highlights some important therapeutic uses of the compounds.